Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1177/1352458511428081
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HHV-6 IgG titer significantly predicts subsequent relapse risk in multiple sclerosis

Abstract: These findings suggest that, in addition to a potential etiological role in MS, HHV-6 infection or the immune response to HHV-6 antigens may have an effect on the risk of MS relapses and possibly on progressive courses of MS. The observed effect was directly related to anti-HHV-6 IgG titers and may indicate that either HHV-6 infection or factors associated with an altered humoral immune response to HHV-6 may have an effect on MS clinical course. Anti-HHV-6 IgG titer may be a useful prognostic factor in relapsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 37 publications
5
46
1
2
Order By: Relevance
“…Peripheral administration of lipopolysaccharide increases inflammatory and oxidative stress in brain, and glial activation in the hippocampus, to a greater extent in aged, compared with young, rats [11]. Consistently, age is associated with increased vulnerability to infections, while infections have been shown to accelerate progression of diseases such as Alzheimer's disease and multiple sclerosis [12], [13]. These findings support the notion that a communication network between the CNS and the periphery exists.…”
Section: Introductionsupporting
confidence: 66%
“…Peripheral administration of lipopolysaccharide increases inflammatory and oxidative stress in brain, and glial activation in the hippocampus, to a greater extent in aged, compared with young, rats [11]. Consistently, age is associated with increased vulnerability to infections, while infections have been shown to accelerate progression of diseases such as Alzheimer's disease and multiple sclerosis [12], [13]. These findings support the notion that a communication network between the CNS and the periphery exists.…”
Section: Introductionsupporting
confidence: 66%
“…Furthermore, the increase of the anti-HHV-6A/B IgG and IgM titers predicts the upcoming clinical relapses. Recently, Simpson et al [30] published that HHV-6A/B infection or the immune response to HHV-6A/B antigens may have an effect on the risk of MS relapses, since the observed effect was directly related to anti-HHV-6A/B IgG titers and may indicate that either HHV-6A/B infection or factors associated with an altered humoral immune response to HHV-6A/B may have an effect on MS clinical course.…”
Section: Discussionmentioning
confidence: 99%
“…A 2012 study of a Tasmanian cohort found HHV-6 IgG titer to be a significant predictor of relapse risk [27]. This was echoed in a 2014 study of a Spanish MS cohort, which reported that a decrease in HHV-6 antibody titers correlated with fewer relapses and less disease progression [28].…”
Section: Traces Of Hhv-6 In the Periphery: Virus Detection And Virus-mentioning
confidence: 99%